Art Research : Under Tua Kak’s Face - Vijitsatitrat, Atipat (DEC Journal : Art and Design, 2023)
This research focuses on the story behind Tua Kak's face, which is an interpretation of murals in the early Ayutthaya period. These murals, located in places such as Buddhaisawan Chapel, Wat Ratchasittharam, and Wat Dusidaram, depict Tua Kak, a human figure in Thai painting whose facial expression is different from other human figures and should be interpreted according to the concept of visual literacy. Tua Kak's emotion on their faces brought to the interpretation and creation of works of art in abstract expressionism, works of art that aim to convey the emotions and perceptions of the artist. These works of art serve as tools for expressing and communicating concepts, emotions, feelings, and meanings to the public. The six resulting paintings express a range of emotions: fear, escape, death, anger, harm, party, fun, and euphoria.